2018
DOI: 10.1016/j.vetimm.2018.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of peripheral blood mononuclear cell populations in periparturient dairy cows that develop metritis

Abstract: Bacterial contamination of the uterus following calving is ubiquitous in the dairy cow, 40% of cows develop postpartum uterine infection, including metritis. While predisposing factors like twinning and dystocia are associated with metritis, it is unclear why some cows remain healthy following calving and others develop uterine infection, negatively impacting animal health, milk production and economic return. Here, we profiled peripheral blood mononuclear cells of cows before calving and during postpartum met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
3
1
0
Order By: Relevance
“…The leukocyte and neutrophil population diminished more in cows suffering clinical endometritis compared to healthy bovine animals. Results of this study were consistent with the reported data on specialized dairy cattle (Islam et al, 2014;Bromfield et al, 2018) from which not only a decline in the population of neutrophils has been informed but also in their immunological capacity and still, a greater loss of such in the cows having metritis (McDougall et al, 2017;Kimura et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The leukocyte and neutrophil population diminished more in cows suffering clinical endometritis compared to healthy bovine animals. Results of this study were consistent with the reported data on specialized dairy cattle (Islam et al, 2014;Bromfield et al, 2018) from which not only a decline in the population of neutrophils has been informed but also in their immunological capacity and still, a greater loss of such in the cows having metritis (McDougall et al, 2017;Kimura et al, 2014).…”
Section: Discussionsupporting
confidence: 91%
“…The cows suffering clinical endometritis had a lower production of milk compared to the healthy cows, which conformed with the majority of the studies consulted (Bromfield et al, 2018;Giuliodori et al, 2013;Wittrock et al, 2011;Dubuc et al, 2011). These similarities can be explained by the fact that all cows with infectious processes reduce the consumption of the dry matter, which decreases the level of available energy for milk synthesis, in comparison with the healthy cows.…”
Section: Metritis Definition Reported Bysupporting
confidence: 76%
“…This coincides with reports that treatment of hypocalcemia with an oral Ca bolus, which results in a transient recovery of serum Ca, did not improve neutrophil functions (Miltenburg et al, 2018), whereas a sustained increase of Ca from calcitriol treatment or prevention of hypocalcemia from feeding a prepartum negative DCAD improved neutrophil function (Vieira-Neto et al, 2017). Postpartum immune dysfunction is associated with increased risk of postpartum diseases, such as metritis (Galvão et al, 2012;Bromfield et al, 2018). We observed that DEFB7, DEFB10, and LAP transcripts in LPS-stimulated neutrophils were decreased in cows that experienced metritis compared with cows that did not.…”
Section: Discussionsupporting
confidence: 87%
“…Given the variability in homeorhetic responses to diverse diseases, identifying common, conserved resistance and tolerance mechanisms should provide insight into resilience in the face of pathogenic microbes from different sites of infection. For example, altered expression profiles of peripheral leukocyte immune regulatory genes related to trafficking, migration, adhesion, energy metabolism, inflammatory mediators, cytokines, cell survival and apoptosis have been associated with both mastitis and uterine disease (13)(14)(15)(16)(17). These findings suggest that changes in peripheral leukocyte gene expression may emphasize mechanisms of immunity that bridge disease states and target tissues.…”
Section: Introductionmentioning
confidence: 99%